Generation Z Customer Orientation as an Element of Social Customer Relationship Management - Olga Lawinska; Anna Korombel (International Journal of Supply Chain Management, 2021)
Building relationships with Generation Z on social media is becoming a challenge for present-day enterprises. Gen Zers have a huge purchasing power, and by 2030 they will be the largest customer base. Customer orientation, as an element of social CRM, enables enterprises to build relationships with customers by appropriately responding to the needs and preferences of their existing and future customers. The aim of the paper was to identify the expectations of surveyed representatives of Gen Zers towards the benefits of customer-company interactions on social media. The study of Generation Z attitudes towards brands on social media is part of broader research conducted by the authors among students in Poland and Great Britain in 2020. The method used in the study was a survey, as part of which the CATI surveying technique was used. For analysis of the study material, descriptive statistics measures were used. Analysis of the collected empirical data provided the basis for verifying the research hypotheses. The findings show what benefits of following a brand on social media by respondents were significant in both the analysed countries. Additionally, the strength of the relationships between the analysed variables and the respondent's gender and place of residence was verified.